Respuesta :

-x - y = 8
2x - y = -1

Ok, we are going to solve this in 2 parts.  First we have to solve for one of the variables in one of the equation in terms of the other variable.  I like to take the easiest equation first and try to avoid fractions, so let's use the first equation and solve for x.

-x - y = 8      add y to each side
-x = 8 + y      divide by -1
x = -8 - y

So now we have a value for x in terms of y that we can use to substitute into the other equation.  In the other equation we are going to put -8 - y in place of the x.

2x - y = -1
2(-8 - y) - y = -1      multiply the 2 through the parentheses
-16 - 2y - y = -1      combine like terms
-16 - 3y = -1            add 16 to both sides
-3y = 15                   divide each side by -3
y = -5

Now we have a value for y.  We need to plug it into either of the original equations then solve for x.  I usually choose the most simple equation.

-x - y = 8
-x - (-5) = 8            multiply -1 through the parentheses
-x + 5 = 8                subtract 5 from each side
-x = 3                      divide each side by -1
x = -3

So our solution set is

(-3, -5)

That is the point on the grid where the 2 equations are equal, so that is the place where they intersect.

ACCESS MORE